IMPLEMENTATION OF MAINTENANCE AND RELIABILITY MANAGEMENT SYSTEM (MRMS) IN PERTAMINA HULU ENERGY SUBHOLDING UPSTREAM (PHE SHU) THROUGH FIELD ASSESSMENT OF ISO 55001 - Khairil Fikri; Djarot B. Darmadi; Deddy Nugraha (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
As part of the integrated efforts that need to be made to achieve the target of becoming a world-class energy company, PHE SHU seeks to carry out the implementation of the Asset Integrity Management System (AIMS) and develop a MRMS which involves a solid team and is able to complete implementation in a timely, effective, efficient and highly competitive manner, to achieve a production target of 1 million bbl/day and 12 bcf/day in 2030 for national energy security referring to the international standard ISO 55001. MRMS is a reference for the governance of the reliability program and maintenance of production facility assets in the Upstream Subholding environment in the operational phase of the Pertamina Group asset management life cycle. identification of Failure Mode Effect Analysis (FMEA) preparation of maintenance strategy programs in the form of task selection for failure mode control based on studies in FMEA namely preparation of detection work programs in rotating equipment in the form of Predictive Maintenance (PdM) activities, task selection of detection programs in static equipment in the form of RBl activity. Task selection prevention in the form of Preventive Maintenance (PM) activities. Failure finding (function test), including determining time intervals for carrying out inspection activities for the PdM, RBI, PM, function test, ORDC (Operator Routine Duty Check List) programs based on the historical failure rate stated in PAREDA in ensuring that Upstream Oil and Gas Assets are optimized, sustainable, safe & reliable operations.